Proteína Bruta para Suínos Machos Castrados Mantidos em Ambiente de Conforto Térmico dos 15 aos 30 kg - Hannas, Melissa Izabel [UNESP]; De Oliveira, Rita Flávia Miranda; Donzele, Juarez Lopes; Ferreira, Aloízio Soares; Lopes, Darci Clementino; Soares, José Luiz; Moretti, Andréa Monica (My University, 2000)
This experiment was carried out to evaluate the requirement of crude protein for initial growing crossbred barrows (Landrace x Large White), from 15 to 30 kg, maintained in thermal comfort. During the experimental period, the room temperature was maintained at 23.1±1.19°C, with relative humidity at 80.6±4.59% and Black Globe Index Humidity at 69.8±1.38. Sixty crossbred barrows with initial average weight of 14.8±0.85 kg and final weight of 29.3±2.4 2kg, were used. A completely randomized blocks design, with five treatments (17.0, 18.0, 19.0, 20.0 and 21.0% of crude protein), six replicates and two animal per experimental unit was used. The dietary crude protein level influenced the daily weight gain and protein and lysine daily intakes that linearly increased. However, the feed:gain ratio linearly decreased. There was no effect of crude protein level on diet and digestible energy daily intakes. The fat deposition rate was not affected, while the protein deposition rate in a quadratic way increased up to the crude protein level of 20.0%. The absolute and relative weight of liver linearly increased as dietary crude protein level increased. The urea plasma concentration was not affected by the dietary crude protein level. Crossbred barrows pigs, from 15 to 30 kg, maintained under thermal comfort, require 20.0% of dietary crude protein, corresponding to 0.901% of total lysine or 57 g of protein/Mcal DE. The plasma urea concentration did not constitute to be an adequate parameter to estimate the crude protein requirement.
Crude Protein for Barrows in Thermal Comfort from 15 to 30 kg
Keywords: Crude protein; Initial phase; Piglets; Thermoneutrality